Performance Appraisal in RBEDS - V.G. Dhanakumar (Journal of Agricultural Extension Management, 2025)
In the management of extension organization two mam mechanisms are involved. One is quality of extension service i.e. value of the work to meet the clients’ accelerating expectations and the other is the management of personnel. This study on the functioning of Rubber Board Extension Delivery System (RBEDS) is concerned with "Quality of Extension Service and its Performance" (QESP). The objective of QESP has shifted from the traditional evaluation, where the organisation is assessed merely as a mechanism to control employees by taking administrative action in respect to overall impact of the organisation. The true measure of an organization’s effectiveness is quality of its service and the performance, as a whole to delight customer